Evaluate the effect of maternal obesity on fetal outcome: an observational study in tertiary health care centre - Gandhi, Vrunda Vijaykumar; Shrivastava, Anjani; Patel, Falguni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Excess weight gain during transitional period leads to an adolescent girl at increased risk of maintaining unhealthy levels of body fat in childbearing years. Prevalence of obesity increases among reproductive age group female and so in pregnant women also with current estimate 20 to 36%. Obesity during pregnancy affects its outcome. It puts mother as well as fetus into complication. Objectives were to find out the effect of obesity on fetal outcome and to study the demographic profile of obese women. Methods: This observational cross-sectional study was conducted during January 2021 to April 2021 for four months in department of obstetrics and gynecology. As per convenient sampling technique 50 women were enrolled as study participants. Data regarding fetal outcome were collected like baby weight, NICU admission, indications for NICU and its outcome. Percentage was used to analyze data. Results: The 16% newborn was having birth weight more than 3.5 kg. 26% new borne were needed NICU admission due to complications like fetal distress, jaundice, prematurity, IUGR, septicemia etc. Conclusions: maternal obesity affects fetal outcome and also one of the risk factor for maternal complications. Pregnancy with high BMI is high risk pregnancy; these should be managed at tertiary health care center with well-equipped HDU and neonatal intensive care unit.